Development of artificial sugarcane seed CP-54 from three cultivars (cv MEX 69-290; cv MEX 68-P-23; cv. CP 72-2086) using polymers in Tabasco, Mexico - Geiner F Álvarez-Sánchez; Heidi L Arias-de la Cruz; Sergio Salgado-García; Samuel Córdova-Sánchez; Hipólito Ortiz-Laurel; Mepivoseth Castelán-Estrada; Rubén García-de la Cruz; Raúl Castañeda-Ceja (Acta Agronómica)
Precision mechanized sowing of sugarcane has been delayed due to germination failures caused in sowing process by pieces of sugarcane, generating economic losses by reducing production. The aim of this study was to evaluate different polymers and cultivars of sugarcane to elaborate artificial seed CP-54, seed germination and quality of sugarcane plants. An experiment was carried out in two stages in experimental field of the Colegio de Postgraduados Campus Tabasco, Mexico. Results indicate that the best physical stage of artificial seed CP-54 was obtained in Mex 69-290, Mex 68-P-23 and CP 72-2086 cultivars encapsulated with starch polymers and sodium alginate. Artificial seed CP-54 germination was 100 and 84% encapsulated with starch and alginate of sodium, in shoots positions 12, 3 and 9, without concerning cultivar. Highest plant height and root length was obtained with encapsulation of starch and sodium alginate. Physical stage of shoots was better in artificial seed made with starch and sodium alginate in the three evaluated sugarcane cultivars and independently of shoot position.